AESTHETICS LANGUAGE IN THE PERFORMING ARTS OF RANDAI KUANTAN IN PANGEAN DISTRICT KUANTAN SINGINGI REGENCY AND ITS IMPLICATIONS FOR LEARNING IN SCHOOLS - Novi Roza Primadhani; Elmustian Elmustian; Zulhafizh Zulhafizh (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This study aims to explain the aesthetics of language in the Randai Kuantan performing arts in Pangean District, Kuantan Singingi Regency and its implications for learning in schools. This type of research is qualitative research using descriptive methods. This research was conducted in Pangean District, Kuantan Singingi Regency. The instruments used were searching, obtaining, and obtaining data by themselves, namely by watching and recording the Randai Kuantan show in Pangean District, Kuantan Singingi Regency using a recording device. Data collection techniques used are recording techniques, interviews, and transcripts. The data source for this research comes directly from the Randai Kuantan show in Pangean District, Kuantan Singingi Regency. The results of the study show that there are five types of diction found in the performing arts of Randai Kuantan, namely: a) denotation, b) connotation, c) abstract, d) concrete, and e) specific.